Circumcision of Hemophilia Patients: Hematological and Socio-Cultural Aspect - Goksel leblebisatan; Ali Bay; Huseyin Kılıncaslan; suleyman cuneyt karakus; nusret soylu; Ali Muhittin Tasdogan (Mediterranean Journal of Hematology and Infectious Diseases)
Objective: Circumcision in patients with hemophilia is a controversial issue in medical professionals and it is affected from place of residence with different social, cultural and religious beliefs.